Միջին հայերենի ընդգրկած ժամանակաշրջանի շրջանաբաժանման նոր փորձ - Մկրտչյան, Գարիկ (ԳԱԱ ԼԻ հրատ․)
Основываясь на том, что в новых лингвистических исследованиях важно дифференцировать разговорный и литературный языки на основе различных контрастов между ними, автор предпринял новую попытку периодизации и разделения подэтапов среднеармянского языка. Автор пришел к выводу, что необходимо провести дифференциацию этапов развития разговорного (устного) и литературного (письменного) среднеармянского языка. Для устно-разговорного среднеармянского языка выделяют три этапа развития – 1. Начальный этап (8-10 вв.), 2. Этап становления и практики (11-14 вв.), 3. Этап практики и завершения (15- 17 вв.). В литературном (письменном) среднеармянском языке выделяют три этапа – 1. Этап зарождения и становления (10-11вв.), 2. Этап практики и развития (12-13вв.), 3. Этап практики и завершения (14-15вв.). Как видно из приведенной класси- фикации, устный (разговорный) среднеармянский охватывает более длительный период, чем письменный (литературный). На весь среднеармянский язык выделяется 10 веков и из них только 6 веков письменный (литературный) язык. - Based on the fact that in new linguistic studies it is essential to differentiate spoken and literary languages based on various contrasts between them the author tried to make a new attempt of periodization and division of sub-stages of Middle Armenian. The author concluded that it is necessary to make a differentiation of development stages of spoken (oral) and literary (written) Middle Armenian language. For oral-conversational Middle Armenian language is separated three development stages – 1. Initial stage (8-10 cc.), 2. Formation and practice stage (11-14 cc.), 3. Practice and termination stage (15-17 cc.). For literary (written) Middle Armenian language is separated three stages – 1. Initiation and formation stage (10-11cc.), 2. Practice and development stage (12-13cc.), 3. Practice and termination stage (14-15 cc.). As it is seen from the above classification oral (spoken) Middle Armenian covers longer period than written (literary). For the whole Middle Armenian language, it is given 10 centuries and from these only 6 centuries cover written (literary) language.
Keywords: Հայ լեզվաբանության պատմություն